Development of a Value-Based VCT Learning Model Al-Washliyahan in The Learning Process at Madrasah Aliyah on North Sumatra - Solihah Titin Sumanti; Yusnaili Budianti; M. Rozali (Badan Litbang dan Diklat Kementerian Agama RI, 2023)
The research problem in this study is that there are only a few schools under the auspices of the Al-Washliyah organization, and there are almost no public schools in North Sumatra that integrate Al-Washliyah values into the learning process. However, Al-Washliyah values are highly aligned with the national education goals of developing an intelligent, characterful, morally upright, and independent society. This is because teachers do not yet have the appropriate strategies and learning models to integrate these values. Therefore, this research aims to develop a VCT (Values-Centered Teaching) learning model based on the ideas of Al-Washliyah figures. The research follows a research and development (R&D) approach. The research design follows the 4D model by Thiagarajan, Semmel, and Semmel. The research subjects consist of 135 Madrasah Aliyah students. Data collection is done through interviews, observations, open questionnaires, expert validation sheets, and practicality assessment sheets for the model. The collected data is then analyzed using SPSS version 25.0. The results of the study show that the developed model has high validity and reliability. Therefore, the developed model can be used as a learning model to integrate the values of Al-Washliyah figures into the learning process.